Identification of Potent, Selective, and Orally Bioavailable Small-Molecule GSPT1/2 Degraders from a Focused Library of Cereblon Modulators - Nishiguchi, Gisele; Keramatnia, Fatemeh; Min, Jaeki; Chang, Yunchao; Jonchere, Barbara; Das, Sourav; Actis, Marisa; Price, Jeanine; Chepyala, Divyabharathi; Young, Brandon; McGowan, Kevin; Slavish, P Jake; et al. (Journal of medicinal chemistry, 2021)
Whereas the PROTAC approach to target protein degradation greatly benefits from rational design, the discovery of small-molecule degraders relies mostly on phenotypic screening and retrospective target identification efforts. Here, we describe the design, synthesis, and screening of a large diverse library of thalidomide analogues against a panel of patient-derived leukemia and medulloblastoma cell lines. These efforts led to the discovery of potent and novel GSPT1/2 degraders displaying selectivity over classical IMiD neosubstrates, such as IKZF1/3, and high oral bioavailability in mice. Taken together, this study offers compound 6 (SJ6986) as a valuable chemical probe for studying the role of GSPT1/2 in vitro and in vivo, and it supports the utility of a diverse library of CRBN binders in the pursuit of targeting undruggable oncoproteins.Whereas the PROTAC approach to target protein degradation greatly benefits from rational design, the discovery of small-molecule degraders relies mostly on phenotypic screening and retrospective target identification efforts. Here, we describe the design, synthesis, and screening of a large diverse library of thalidomide analogues against a panel of patient-derived leukemia and medulloblastoma cell lines. These efforts led to the discovery of potent and novel GSPT1/2 degraders displaying selectivity over classical IMiD neosubstrates, such as IKZF1/3, and high oral bioavailability in mice. Taken together, this study offers compound 6 (SJ6986) as a valuable chemical probe for studying the role of GSPT1/2 in vitro and in vivo, and it supports the utility of a diverse library of CRBN binders in the pursuit of targeting undruggable oncoproteins.